Legal Policy on Strengthening the Existence of the Indonesian National Border Management Agency (BNPP RI) in Resolving Border Area Disputes of the Unitary State of the Republic of Indonesia Based on Law Number 43 of 2008 Concerning State Territory - Belly Isnaeni; Edi Sofwan (Faculty of Law, Universitas Pekalongan, 2025)
The method used in this study is a normative research type based on the study of border area law analysis, research specifications focus on discussing the challenges and existence carried out by the BNPP RI. Primary data from the study and analysis of legislation and secondary data based on in-depth analysis of literature sources in books, journals, proceedings and other scientific article sources. The analysis in this study uses descriptive analysis of laws and cases that have occurred in the field analyzed based on sources of settlement of agreements and decisions. The results of the first study, that BNPP has many challenges related to the problems of border disputes both domestically and abroad, these challenges can be resolved by BNPP. However, the limitations of budget problems, human resources, coordination between border areas in all provinces that are too broad and the development of technology for borders between regions is still not optimal. Second, the existence of the National Border Management Agency of the Republic of Indonesia (BNPP RI) must be strengthened, based on Article 14 Paragraph (2) BNPP is directly responsible to the President, but in its implementation there needs to be coordination with other institutions and Regional Governments in carrying out its duties and authorities. as if it does not have the principle of independence in accordance with the mandate of the law.